2008
DOI: 10.1161/hypertensionaha.108.110296
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Intermittent Hypoxia and Developmental Programming of Hypertension in Spontaneously Hypertensive Rats

Abstract: Abstract-Obstructive and central apneas during sleep are associated with chronic intermittent hypoxia (CIH) and increased cardiovascular morbidity. Spontaneously hypertensive rats exposed to CIH during postnatal days 4 to 30 develop exaggerated hypertension as adults. We hypothesized that reactive oxygen species and altered L-Ca 2ϩ channel activity may underlie the postnatal programming of exaggerated blood pressure and cardiac remodeling. Newborn male spontaneously hypertensive rats were exposed to CIH (10% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Moreover, our findings show that when MnTMPyP was injected daily beforehand into SHR exposed to IH for 30 consecutive days, the cardiomyocyte necrosis and loss caused by CIH were significantly reduced. This phenomenon is similar to those found in the other studies that showed treatment with MnTMPyP reduced ROS-triggered cell death [21,27]. Therefore, our findings suggest that cardiomyocyte death due to CIH is mainly caused by an increase in free radicals and a decrease in antioxidant capacity, allowing excess free radicals to cause oxidative damage to cardiomyocytes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our findings show that when MnTMPyP was injected daily beforehand into SHR exposed to IH for 30 consecutive days, the cardiomyocyte necrosis and loss caused by CIH were significantly reduced. This phenomenon is similar to those found in the other studies that showed treatment with MnTMPyP reduced ROS-triggered cell death [21,27]. Therefore, our findings suggest that cardiomyocyte death due to CIH is mainly caused by an increase in free radicals and a decrease in antioxidant capacity, allowing excess free radicals to cause oxidative damage to cardiomyocytes.…”
Section: Discussionsupporting
confidence: 92%
“…In each group, WKY and SHR were randomly assigned to two subgroups (n=5 in each subgroup), perfusion with propidium iodide (PI, Sigma, USA) and phosphate-buffered saline (PBS), except the group of IH30 combined with MnTMPyP, which was assigned to perfusion with PI. Rats were given daily intraperitoneal injections of 10 mg/kg MnTMPyP (Sigma; St. Louis, MO, USA) 10 min before daily IH exposure initiation [21]. All surgical and experimental procedures were approved by the Institutional Animal Care and Use Committee of Tzu Chi University.…”
Section: Animal Preparationmentioning
confidence: 99%
“…The mechanisms underlying these responses are unclear, and whether IH alters the activity or function of vascular ion channels has not been rigorously studied. The involvement of L-type VGCCs in IH-induced outcomes in the systemic circulation is indirectly supported by data demonstrating aggravated hypertension in spontaneously hypertensive rats following postnatal exposure to IH and prevention of this result by the L-type VGCC blocker, nifedipine (208). Moreover, indirect and uncomprehensive evidence suggests that exposure of a brain endothelial cell line to IH leads to activation of NSCCs with subsequent involvement of store-operated Ca 2ϩ release mediated by IP 3 R and RyR (232).…”
Section: Circulatory Systemmentioning
confidence: 94%
“…1). Cyclic polyamine (aza crown ethers)-based SOD mimics were characterized in details in vitro and in vivo (295). Mn salen derivatives were investigated as well (88).…”
Section: B Antioxidantsmentioning
confidence: 99%